Bicycle and pedestrian manual count programs: Assessing the feasibility and value for measuring local active transportation work. (March 2020) - Ray, Anastazjia F. Tasha; Pelletier, Jennifer E.; Zukoski, Ann P.
Abstract: Introduction: Promoting walking and bicycling has been a major focus in the US in recent years. Bicyclist and pedestrian manual counting programs are used to measure how many people are walking and bicycling in specific locations and their characteristics. The purpose of this study was to understand how communities use this data and assess the potential to use manual count data for assessment and evaluation. Methods: Six communities in Minnesota were selected to participate in this study. One semi-structured interview per community was conducted with local public health staff who participated in manual counts in 2012, 2014, and 2016. Interviews were transcribed and analyzed using a thematic analysis approach. Results: Communities described their motivation to conduct counts, management of existing programs, and how they interpreted and used the count data. Among the many uses of the data discussed were documenting use of facilities, allocating resources, assessing efficiency of investments or need for safety interventions, informing or conducting research, and community engagement. Communities also described how the setting and circumstances that exist in the community affect both data interpretation and implications of the data as well as barriers, facilitators, and technical assistance needs for collecting and using count data effectively. Conclusions: Communities may need technical assistance to know how to use data collected through bicyclist and pedestrian manual counting. However, with appropriate instruction and assistance, counts are a feasible assessment tool for local active transportation (bicycling and walking) promotion efforts. However, contextual information about the setting and circumstances that exist in local communities is necessary to properly interpret and use count data and therefore is also necessary when using counts for assessment or evaluation. This method supports equity as manual counts do not require expensive equipment, and are relatively easy to implement. Highlights: Manual counts are valuable tools for planning and evaluation but are underused. Despite increased availability of automatic counting a role still exists for manual counts. Manual counts can provide valuable community context and engagement. Findings suggest a lack of motivation to evaluate without a positive outcome. Communities value education and resources for management and use of data.